Risky firms and fragile banks: Implications for macroprudential policy - Tommaso Gasparini; Vivien Lewis; Stéphane Moyen; Stefania Villa (Deutsche Bundesbank, 2024)
Increases in firm default risk raise the default probability of banks while decreasing output and inflation in US data. To rationalize the empirical evidence, we analyse firm risk shocks in a New Keynesian model where entrepreneurs and banks engage in a loan contract and both are subject to default risk. In the model, a wave of corporate defaults leads to losses on banks' balance sheets; banks respond by selling assets and reducing credit provision. A highly leveraged banking sector exacerbates the contractionary effects of firm defaults. We show that high minimum capital requirements jointly implemented with a countercyclical capital buffer are effective in dampening the adverse consequences of firm risk shocks.
Keywords: E44; E52; E58; E61; G28; 330; bank default; capital buffer; firm risk; macroprudential policy